The THE EFFECT OF DEBT, OWN CAPITAL AND NON-STOCK SAVINGS ON COOPERATIVE RENTABILITY - Agustinus Supriyanto (MBIA, 2019)
The purpose of this study was to obtain an overview of the effect of Debt, Own Capital and Non-Stock Savings on profitability (ROA) and which variables were most dominant in KSP Kopdit Rukun, Sentosa, Setia Kawan, Karya Kasih and Patra Pertamina and to analyze these variables simultaneously and partially. In this study debt, own capital and non-stock savings are independent variables (X), while Profitability (ROE) is the dependent variable (not free). The type of data used in this study is secondary data that is quantitative. Data sources are financial statements for 2012 to 2017. The method used for this research is multiple linear regression, followed by a partial and simultaneous significance test through t test and F test. Research results within 5 years concluded as follows: first, KSP Kopdit Rukun that debt and capital alone have no significant effect on ROE, while non-stock savings have a significant and simultaneous effect that debt, own capital and non-stock savings have an influence but not significant, while Sentosa, Setia Kawan, Karya Kasih and Patra pertamina have partial or simultaneous influence but not significant. For KSP Kopdit Rukun, Sentosa, Setia Kawan, Karya Kasih and PATRA Pertamina, it is better to use internal and external funding sources according to their conditions, in order to obtain maximum profitability (ROE).